Implementing quotas in university admissions: An experimental analysis - Dorothea Kübler; Sebastian Braun; Nadja Dwenger; Alexander Westkamp (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
Quotas for special groups of students often apply in school or university admission procedures. This paper studies the performance of two mechanisms to implement such quotas in a lab experiment. The fi rst mechanism is a simplifi ed version of the mechanism currently employed by the German central clearinghouse for university admissions, which first allocates seats in the quota for top-grade students before allocating all other seats among remaining applicants. The second is a modifi ed version of the student-proposing deferred acceptance (SDA) algorithm, which simultaneously allocates seats in all quotas. Our main result is that the current procedure, designed to give top-grade students an advantage, actually harms them, as students often fail to grasp the strategic issues involved. The modi ed SDA algorithm signifi cantly improves the matching for top-grade students and could thus be a valuable tool for redesigning university admissions in Germany.
Keywords: C78; C92; I20; 330